Sympathy for the devil? Exploring flexicurity win-win promises - Pablo de Pedraza; Marcos Álvarez-Díaz; Marcos Dominguez Torreiro (IZA Journal of Labor Policy, 2019)
Flexicurity is the combination of more flexibility for employers and more security for workers. It is a complex and multifaceted phenomenon that lacks a well-developed monitoring framework or a statistically consistent grouping of the indicators. First, this paper proposes a conceptual framework by building upon the Wilthagen and Tros (2004) flexicurity matrix and the Danish Golden Triangle. It constructs flexicurity 'drivers' by pooling together variables that are conceptually related to each other and a specific type of flexibility or security. Then, it obtains statistically consistent aggregate measures for each driver and selects three drivers that represent the three corners of the Danish 'golden triangle': external numerical flexibility, employment security, and income security. It conducts an empirical analysis on the evolution of the selected flexicurity drivers over time and across European Union (EU) countries and on the relationship between selected flexicurity drivers and social outcomes from the Social Scoreboard of the European Pillar of Social Rights. It finds evidence of convergence on external numerical flexibility and polarization on employment and income security across the EU. It finds that higher flexibility at the onset of the crisis contributed to a reduction in the unemployment rates after the crisis, while a more generous welfare system contributed to reducing poverty. Employment security, however, appears to be linked to the presence of higher levels of income inequality after the crisis.
Keywords: J0; J4; J5; C5; 330; flexicurity; European Pillar of Social Rights; unemployment; employment; poverty; inequality